SAT0583 The immediate effect of a soft knee brace on dynamic knee instability in persons with knee osteoarthritis. (12th June 2018) - Cudejko, T.; van der Esch, M.; Schrijvers, J.; Richards, R.; Wrigley, T.; van den Noort, J.; van der Leeden, M.; Roorda, L.D.; Lems, W.; Harlaar, J.; Dekker, J.
Abstract : Background: Wearing a soft knee brace has been shown to reduce self-reported knee instability in persons with knee osteoarthritis (OA). 1 There is a need to assess whether a soft knee brace has a beneficial effect on objectively assessed dynamic knee instability as well. Objectives: The aims of the study were: (i) to evaluate the immediate effect of a soft knee brace on dynamic knee instability, and (ii) to assess the difference in effect between a tight and a non-tight knee brace in persons with knee OA. Methods: A within-subject cross-over design was used, comparing wearing a soft knee brace with not wearing a soft knee brace, and comparing wearing a tight brace (standard fit) with wearing a non-tight brace (one size larger). The order of brace type was randomised. Participants walked, both without and with the brace, on a treadmill, which is integrated in the GRAIL system, placed in a virtual reality environment (GRAIL system, MOTEKForce Link, The Netherlands). Participants were subjected to two tasks: (i) level walking and (ii) walking with mechanical perturbations on the treadmill. Mechanical perturbations on the treadmill comprised five lateral and five medial translations (2 cm displacements) of the treadmill belts occurring during 20%–50% of the gait cycle. During the walking trials, 3D movement of the lower legs, pelvis and trunk were captured via markers on anatomical landmarks at 100 Hz using a motion-capture system (Vicon, Oxford, United Kingdom). The outcome measure was dynamic knee instability, expressed by the Perturbation Response (PR), i.e. a biomechanics based measure reflecting deviation in the mean knee varus-valgus angle after a controlled mechanical perturbation, standardised to the mean (standard deviation) varus-valgus angle during level walking. Lower PR values indicate less deviation in the mean varus/valgus angle. Linear mixed-effect model analysis was used to evaluate the effect of a brace on dynamic knee instability. Results: Thirty-eight persons with knee OA and self-reported knee instability from the Amsterdam Osteoarthritis Cohort participated in the study. Wearing a brace significantly reduced the PR compared to not wearing a brace (p<0.05). The PR value reduced from 0.48 when not wearing a brace to 0.32 when wearing a brace. This means that wearing a brace resulted in a reduction of 33% in dynamic knee instability compared to not wearing a brace. There was no difference between a non-tight and a tight brace (p>0.05). Conclusions: This study is the first to report that wearing a soft brace results in an improvement of objectively assessed dynamic knee instability, beyond the previously reported subjective improvement. Reference: [1] Cudejko T, van der Esch M, van der Leeden M, van den Noort JC, Roorda LD, Lems W, Twisk J, Steultjens M, Woodburn J, Harlaar J, Dekker J: The immediate effect of a soft knee brace on pain, activity limitations, self-reported knee instability, and self-reported knee confidence in patients with knee osteoarthritis. Arthritis Res Ther2017;19:260. Disclosure of Interest: None declared